2021
DOI: 10.1016/j.surg.2020.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroidectomy on circulating angiogenic cytokines in papillary thyroid carcinoma and benign goiter: Potential for new biomarkers?

Abstract: Background: Circulating angiogenic factors have been associated with clinical outcomes of papillary thyroid carcinoma, although they may also be released in the context of benign multinodular goiter. We sought to investigate the effect of thyroidectomy on the activity and importance of multiple circulating angiogenic factors in papillary thyroid carcinoma and benign multinodular goiter. Methods: Between May 2015 and December 2016, patients scheduled for total thyroidectomy for papillary thyroid carcinoma or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…It should be noted that 40% of the PTC cohort had stage III or IV disease. Ria et al reported signi cantly greater levels of VEGF-A in PTC and MNG patients as compared to healthy subjects [17]. Our results did not demonstrate differences between the studied groups.…”
Section: Vegf-acontrasting
confidence: 63%
See 1 more Smart Citation
“…It should be noted that 40% of the PTC cohort had stage III or IV disease. Ria et al reported signi cantly greater levels of VEGF-A in PTC and MNG patients as compared to healthy subjects [17]. Our results did not demonstrate differences between the studied groups.…”
Section: Vegf-acontrasting
confidence: 63%
“…Niedzwiecki et al did not observe overall differences but in subgroup analysis levels of Ang-2 were signi cantly lower in PTC patients [14]. In a recent study with similar exclusion criteria as our own study design, levels of Ang-2 were elevated in PTC and benign thyroid disease compared to healthy controls [17]. Postoperative levels also exhibited a marked decline in both groups.…”
Section: Discussionsupporting
confidence: 47%
“…Recent scientific evidence has shown that angiogenic factor profiling can be useful in the deepening of tumor biological tools and highly useful in strengthening therapeutic strategies for papillary thyroid carcinoma (PTC) [ 158 ]. PTC patients revealed substantial bFGF levels when compared to healthy controls; however, a total thyroidectomy surgical procedure resulted in the successful decreasing of bFGF overexpression [ 158 ]. Moreover, miRNAs such as miR-27b-3p and miR-195 were probed in the context of thyroid cancer [ 159 , 160 ].…”
Section: Bfgf and Cancermentioning
confidence: 99%
“…Natural inhibitors of MMPs are the tissue inhibitors of metalloproteinases (TIMPs), produced and released in the tumor microenvironment [ 93 ]. Published data from our group indicate that the MMPs’ proangiogenic and pro-tumoral activities are related to the balance of MMPs and TIMPS in the microenvironment, and that the switch toward an invasive phenotype is mainly due to increased MMP production and release, and not to the reduction of TIMPs ( Figure 1 ) [ 94 , 95 ].…”
Section: The Thyroid Cancer Microenvironmentmentioning
confidence: 99%
“…A possible application for this aim is the assay of miRNA in exosomes, especially miR-21-5p [ 52 , 125 ], which is a decisive proangiogenic factor produced by thyroid cancer cells. VEGF-A and PDGF-BB have been recently indicated as potential circulating biomarkers of PTC treatment [ 94 ].…”
Section: Angiogenesis and Prognosismentioning
confidence: 99%